The mediating effect of self-efficacy and physical activity with the moderating effect of social support on the relationship between negative body image and depression among Chinese college students: a cross-sectional study - Ye Yuan; Yanling Tu; Yuqi Su; Lei Jin; Yu Tian; Xuesong Chang; Ke Yang; Haiyun Xu; Junyi Zheng; Daili Wu (BMC Public Health)
Abstract Background Fitness to maintain an ideal body shape is becoming increasingly popular among college students. However, it also leads to many mental health issues. This study explores the pathways through which negative body image affects depression in college students. It also examines possible means of implementing depression interventions in college populations through the mediating roles of self-efficacy and physical activity, and the moderating role of social support. Method The present study employed a convenience sampling method to collect data from 600 university students using the Body Image Scale, Self-Efficacy Scale, Physical Activity Scale, General Social Support Scale and Depression Self-Rating Scale. Data analysis and structural equation modeling were conducted using SPSS, M-plus and R software. Result The result indicate that negative body image is positively correlated with depression. Self-efficacy and physical exercise play a chain mediating role between body image and depression. Additionally, social support moderates the effects of self-efficacy by predicting the pathway through which physical activity effects depression. Conclusion The study suggest that individuals with a negative body image are more prone to depression and that physical exercise can help alleviate their depressive symptoms. Self-efficacy is an important mediator, and social support moderates adherence to physical exercise. Therefore, attention should be paid to the mental health issues of college students with negative body images.